THE EFFECT OF SCHOOL-BASED MANAGEMENT AND DEMOCRATIC PRINCIPAL'S LEADERSHIP ON THE PERFORMANCE OF CLASSROOM TEACHERS IN THE PUBLIC ELEMENTARY SCHOOL - Unun Magfiroh; Santoso Santoso; Su'ad Su'ad (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2021)
This study aims to analyze the effect of School-Based Management and democratic principal's leadership on the performance of classroom teachers in the Public Elementary Schools of Gugus Kartini, Sub-District of Kota Kudus. The research method used is a quantitative approach using a causal research design to determine the relationship between independent variables (X) and the dependent variable (Y). The independent variable is School-Based Management and the democratic leadership of the principal, and the dependent variable is the performance of classroom teachers. The research was conducted in 3 SD Negeri Gugus Kartini, Kudus City District. Data was collected by means of a questionnaire. Data analysis was carried out using descriptive percentage analysis, prerequisite analysis, and statistics with regression, correlation, determination of the coefficient of determination, and hypothesis testing. The results found that there is a significant effect of School-Based Management on the performance of classroom teachers, with R = 0.381 and the effect at 14.5%. There is a significant effect of democratic principal's leadership on the performance of classroom teachers, with R = 0.260 and the effect at 6.8%. There is a significant effect of School-Based Management and democratic principal's leadership on the performance of classroom teachers, with R =  0.483 and the effect at 23.4%.